Relationship between COVID-19 vaccination and sleep quality: A cross-sectional study (Research, Society and Development, 2024)
Aim: To evaluate the potential effects of COVID-19 vaccination on the perception of sleep quality among various categories of vaccinated individuals, as well as among unvaccinated individuals. Methods: A cross-sectional, quantitative, and descriptive approach was used, targeting participants of both genders who completed an online form on Google pertaining to sociodemographic information, sleep quality, vaccination status, and other factors related to quality of life. Inclusion criteria involved participants over 18 years of age who consented to the Informed Consent Form. The study was conducted with the approval of the Research Ethics Committee of UEPB, with the CAAE number: 57982422.1.0000.5187. Data were analyzed using descriptive statistics and correlation matrix. Results: The sample consisted of 96 adults, ranging from 19 to 66 years old, with most participants being female, accounting for 77.1% of the sample. Regarding the effects of vaccination on sleep, a high homogeneity in the data was observed, with no correlation found between vaccine doses and sleep quality. Additionally, concerning the feeling of tranquility and relaxation after vaccine administration, 13.5% reported feeling so after the first dose, 28.1% after the second dose, 22.9% after the third dose, and 43.8% claimed not to notice any difference. The research indicated that 60.4% of participants reported an improvement in quality-of-life post-vaccination. Final Considerations: These results underscore the importance of disseminating the benefits of vaccination that extend beyond immunization, positively influencing not only physical well-being but also psychological and social well-being, key components of quality of life.